Effect of fermentation duration on rice straw (Oryza Sativa L) in bioethanol quality - Yusron Rifky; Umami Mahrus; Ahmad Sabaruddin; Arendra Anis; Irawan Ibnu (BIO Web of Conferences)
Rice straw (Oryza sativa L.) can be used to produce bioethanol. Bioethanol is a liquid alternative fuel that has the potential to serve as a substitute for, and potentially even replace, fossil fuels. Hence, considering the substantial amount of agricultural waste generated and its underutilization, it is feasible to transform agricultural waste into a liquid fuel known as bioethanol. Rice straw is a type of agricultural waste that can be transformed into bioethanol, a form of liquid fuel. The rice straw conversion process involves the utilization of hydrolysis, fermentation, and distillation techniques for the production of liquid fuel. This study employed an experimental approach, utilizing yeast quantities of 20% and 30% as the fermentation substrate. Additionally, variations in fermentation duration were investigated, specifically 7, 8, 9, and 10 days. This research aims to assess the quality of liquid solid fuel (Bioethanol) by measuring its heating value and flash point. Rice straw is used as the raw material for this investigation. Bioethanol, a liquid solid fuel, can serve as a viable substitute for fossil fuels in several applications. The time of fermentation has a direct correlation with the production of bioethanol. The maximum bioethanol yield obtained in this study was 34.4%, which was achieved after 9 days of fermentation. This substance has a flashing point of 21°C. The density of the fermentation at 9 days is 0.79 gr/ml, which is the lowest recorded value.